HUBUNGAN DUKUNGAN SOSIAL DENGAN PENYESUAIN DIRI SISWA BROKEN HOME DI SMKN 4 PADANG SEMESTER GENAP TAHUN AJARAN 2025/2026 - Novita Yulia Nengsih; Linda Fitria; Ridho Rismi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Novita Yulia Nengsih, “The Relationship between Social Support and the Adjustment of Broken Home Students at SMK Negeri 4 Padang, Even Semester of the 2025/2026 Academic Year”, Undergraduate Thesis, Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Putra Indonesia University